PHOTOMETRIC RESEARCH OF SEYFERT GALAXIES MRK 766, MRK 6, MRK 1040, MRK 1513 - S. Shomshekova; E. Denissyuk; R. Valiullin; A. Kusakin; I. Reva; Ch.Omarov (Academic Scientific Journal of Computer Science, 2019)
The paper presents the results of the photometric observations of the Seyfert galaxies from the Markarian list: MRK 766, MRK 6, MRK 1040, MRK 1513. The observations were carried out on “the Eastern“ 1- meter telescope, located at the Tien-Shan Astronomical Observatory of the Fesenkov Astrophysical Institute. The observational data were processed using the MaximDL6 software package. The brightness was estimated by differential photometry, using standard stars in the vicinity of galaxies. This paper presents the light curves of the galaxies: Mrk 766, Mrk 6, Mrk 1040, Mrk 1513. It has been noted, that in Mrk 766, there is a tendency to a gradual weakening of the brightness in the three filters. Photometric changes of the galaxy Mrk 6 during 2016-2019 occurred synchronously in all three filters. The weakening of its brightness began in 2017and by 2019 it reached 0m.9. During the investigation period, irregular brightness fluctuations were registered in galaxies Mrk 1040 and Mrk 1513 with amplitudes of 1m 0 and 0m.8, respectively.